Hypocholesterolemia in liver and cardiovascular disease: Friend or foe? - Valentina Flagiello; Emelie Barreby; Umberto Vespasiani‐Gentilucci; Stefano Romeo (Journal of Internal Medicine, 2026)
Abstract Hypocholesterolemia is perceived as benign given its association with lower cardiovascular risk. However, genetic and epidemiological evidence indicates that persistently low levels of low‐density lipoprotein cholesterol (LDL‐C) and apolipoprotein B (ApoB) arise from distinct biological mechanisms with different hepatic implications. Hypocholesterolemia may reflect either impaired hepatic assembly and secretion of ApoB‐containing lipoproteins or enhanced peripheral clearance of circulating lipoproteins, with divergent outcomes. Genetic defects disrupting ApoB‐dependent lipoprotein secretion, notably variants in apolipoprotein B gene ( APOB ) and microsomal triglyceride transfer protein gene ( MTTP ), limit hepatic lipid export and promote intrahepatic triglyceride retention, predisposing to steatosis and progressive liver disease without metabolic risk factors. Hypocholesterolemia driven by increased lipoprotein clearance, as observed with loss‐of‐function variants in proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) or angiopoietin‐like protein 3 ( ANGPTL3 ), produces lifelong LDL‐C reduction that is cardioprotective without consistent evidence of adverse hepatic outcomes. Cohort and sequencing studies demonstrate an increased burden of liver disease in secretion‐driven hypocholesterolemia but not in clearance‐driven phenotypes. These findings indicate that clinical consequences are determined by the underlying biological mechanism rather than the degree of cholesterol lowering. After exclusion of secondary causes, genetic testing may be considered in people with metabolic dysfunction‐associated steatotic liver disease (MASLD) and hypocholesterolemia to clarify the mechanism, guide follow‐up, and enable family cascade screening. In impaired secretion phenotype forms, lifelong MASLD monitoring may be warranted, with timely consideration of therapy if liver disease progresses. In clearance‐mediated phenotypes, management should follow standard MASLD risk stratification and care, without additional surveillance related to the genetic defect.